2020
DOI: 10.1016/j.amsu.2020.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Does elective orthopaedic surgery in pandemic era increase risk of developing COVID-19? A combined analysis of retrospective and prospective study at Cipto Mangunkusumo Hospital, Jakarta, Indonesia

Abstract: Background To date, no recommendations have been published on when and how to start again carrying out elective, non-urgent surgery on COVID-19-negative patients after the epidemic peak has been reached in a given country or region and the pressure on healthcare facilities, healthcare workers and resources has been released by so far that elective surgery procedures can be safely and ethically programmed again. This study aims to investigate whether elective orthopaedic surgery will increase the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
1
7
0
1
Order By: Relevance
“…The first case of COVID-19 in Indonesia was on March 2, 2020 [6]. As of March 14, 2021, positive confirmed cases in Indonesia reached 1,414,741 cases with 38,329 deaths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first case of COVID-19 in Indonesia was on March 2, 2020 [6]. As of March 14, 2021, positive confirmed cases in Indonesia reached 1,414,741 cases with 38,329 deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Center for Disease Control and Prevention (CDC) are also a consideration for delaying planned operations. According to CDC data, about 25% of people who contracted COVID-19 did not show any symptoms [6], [8].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, various standard operating procedures were applied for patient screening until protocols in surgery or treatment of orthopedic patients with COVID-19. Kamal et al found that elective orthopedic surgery might not be associated with increased cases of COVID-19 cases [14].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first confirmed case of COVID-19 in Indonesia in early March 2020, all aspects of medical services in Indonesia have been affected [8]. It is ranged from primary care service until surgery service [9], [10], [11]. There were several previous papers that reported the effect of the COVID-19 pandemic to THA/TKA surgical service from other countries [12], [13].…”
Section: Discussionmentioning
confidence: 99%